Human Amnion Epithelial Cells do Not Abrogate Pulmonary Fibrosis in Mice with Impaired Macrophage Function - Sean V. Murphy; Suzane C. Shiyun; Jean L. Tan; Siow Teng Chan; Graham Jenkin; Euan M. Wallace; Rebecca Lim (2012)
Since current treatments for both acute and chronic lung diseases are less than ideal, there has been recent interest in the use of cell-based therapies for inflammatory lung disease. Specifically, human amnion epithelial cells (hAECs) have been shown to reduce bleomycin-induced lung injury and prevent subsequent loss of respiratory function, primarily through modulation of the host immune response. The precise mechanisms of this effect remain unclear. We aimed to investigate the potential of hAECs to mitigate bleomycin-induced lung injury in surfactant protein C deficient ( Sftpc -/- ) mice, which are highly susceptible to pulmonary injury as a result of impairment of macrophage function. Primary hAECs were administered to wild-type ( Sftpc +/+ ) and Sftpc -/- mice 24 h after exposure to bleomycin. Compared to Sftpc +/+ mice receiving bleomycin alone, Sftpc +/+ mice administered hAECs 24 h after bleomycin exposure had decreased expression of proinflammatory genes, decreased macrophage and neutrophil infiltration, fibrosis, collagen content, and α-smooth muscle actin as well as a significant improvement in lung function. Compared to Sftpc -/- mice given bleomycin alone, Sftpc -/- mice administered hAECs 24 h after bleomycin did not have a decrease in inflammatory gene expression or a reduction in macrophage pulmonary infiltration. Subsequently, Sftpc -/- mice did not show any decrease in pulmonary fibrosis or improvement of lung function after hAEC administration. The ability of hAECs to mitigate bleomycin-induced lung injury is abolished in Sftpc -/- mice, suggesting that hAECs require normal host macrophage function to exert their reparative effects.